Perencanaan Wajib Belajar 12 Tahun - Alfian Khadafi; Siti Qomariyah; Doa Fajarwati (Lembag, 2025)
In the process of education is not quite held in a short time. Mastery of science-pionlement requires extra time, energy even money. When calculated in the quantity of education time is held a lifetime. But when viewing education policies in a country, one of Indonesia education is required to be in total period of 12 years. None other, the 12-year education is a form of preparation manifestation to be a better person and benefits. But the 12-year-old is not as easy as reversing the palm, it is necessary to mature and systematic planning. That's what the reason for this paper is made. The research method used in this research is the qualitative research method, precisely library research (library study). With Data Collection Techniques and Data Analysis Technique in the form of content analysis (content analysis). The results of this study indicate that education is a most important period of formal education required by the law of each country, education is required to all children under the age of the state, the program must learn to have legal basis in the 1945 Constitution. There are several things that support the 12-year-old study. From regulation, 12-year study must be supported through the constitution and various relevant refrigerators with education. The 1945 Constitution of Article 31 paragraph (2) states that